Effective Scientific Presentations Across Formats: A Modern Guide for Science Trainees and Researchers - Grambow, Steven C.; Weinfurt, Kevin P (Advances in Social Sciences Research Journal, 2024)
This paper presents a comprehensive tutorial on delivering effective scientific presentations in the modern era, addressing a landscape altered by the COVID-19 pandemic. The shift to virtual and hybrid formats has fundamentally changed the norms of how scientific findings are shared, creating new challenges and opportunities for presenters. Drawing from over a decade of experience teaching and refining presentation skills, we address a soft-skill gap in clinical and translational science training. The tutorial outlines four key topics: (1) identifying your scientific story, (2) using effective slide design, (3) presenting data, and (4) delivering your presentation. These lessons, developed through extensive seminars and individual coaching at various academic institutions, enable researchers to enhance communication and audience engagement across presentation formats. Our approach, informed by cognitive processing and data visualization principles, has adapted to the new reality of virtual and hybrid presentations. This work contributes practical insights for optimizing presentation skills in this changed communication landscape. By offering actionable recommendations derived from real-world experience, this tutorial provides valuable guidance for science trainees, junior faculty, and established researchers across disciplines. It aims to equip readers with the necessary tools to deliver compelling scientific presentations in any format, advancing effective academic discourse in an era where virtual and hybrid presentations have become the norm.